(untitled) (KENOSIS: Jurnal Kajian Teologi, 2024)
Abstract Tolerance should be a two-way communication between different groups in society, not just from the minority to the majority. Interreligious and intercultural religious education can contribute significantly to the deep tolerance of Indonesian society. This paper identifies and analyzes the potential collaboration between postcolonial imagination and liberating interdependence in interreligious-intercultural Christian religious education, using qualitative research based on a literature study with postcolonial analysis supported by interviews with five Christian religious leaders in Indonesia. Postcolonial imagination and liberating interdependence result in interreligious and intercultural education that promotes dialogue, liberation, tolerance, and social justice in Indonesia’s pluralistic context. This educational approach will widen the learning space so that it is not limited to the classroom or church walls only. A safe learning space will be created for various local narratives in their encounters with diverse religious stories and their connection to economic structure, politics, race, and gender. This learning space also allows both women and men to share their life stories in connection to God the Liberator. Keywords: Education, Interreligious, Intercultural, Postcolonial Imagination, Interdependence.